2016
DOI: 10.1212/cpj.0000000000000313
|View full text |Cite
|
Sign up to set email alerts
|

Adding an advanced practice provider to a neurology practice

Abstract: Advanced practice providers (APPs) are qualified medically licensed health care providers, including nurse practitioners (NPs), physician assistants (PAs), nurse anesthetists, certified nurse-midwives, and clinical nurse specialists, who can function either independently or alongside a physician in populationcentered care models, disease management integration, care coordination, or in the provision of direct patient care. They also can improve revenue and reduce physician burnout. The use of APPs in the pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Neither the PA nor the PNP disciplines have specific neurology or neuroscience boards available (Black, Pearlman, & Khoury, ), and there is variability in the training process of APPs in specialised fields (Day, Boden, Knott, O'Rourke, & Yang, ). Future research may benefit from studying the impact of both gender and the education and training differences of the disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…Neither the PA nor the PNP disciplines have specific neurology or neuroscience boards available (Black, Pearlman, & Khoury, ), and there is variability in the training process of APPs in specialised fields (Day, Boden, Knott, O'Rourke, & Yang, ). Future research may benefit from studying the impact of both gender and the education and training differences of the disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In 2018, an AAN survey of practicing APPs found that 87% had some neurology lectures in school, yet only 30% had a course and 25% had a clinical rotation. 7 Thus, APPs enter neurologic practice with limited formal exposure to neurology, which may limit their effective integration on clinical teams. 1,5,7 Options for postgraduate training are limited.…”
mentioning
confidence: 99%
“…7 Thus, APPs enter neurologic practice with limited formal exposure to neurology, which may limit their effective integration on clinical teams. 1,5,7 Options for postgraduate training are limited. 8 Although there are over 700 degree-granting APP programs, only 15 postgraduate programs exist, of which 3 focus on neurology.…”
mentioning
confidence: 99%
See 2 more Smart Citations